Pemanfaatan Limbah Bekas (Rongsokan) Sebagai Penghasilan Utama Masyarakat Desa Panguragan Cirebon - Dhika Dzulkarnain Wibisono; Dewi Ariyani (Institut Teknologi dan Bisnis Asia Malang, 2022)
The purpose of this article boils down to the potential of the village in recycling used Rogsokan goods to become the main source of income for the Panguragan village community, Cirebon. Where people collect junk from various regions and resell it to large manufacturers, so it's not surprising that many people run this business and make it the big boss who can be said to be able to lift the economic sector of the community. The results of the observations showed positive results where the economy was better in Panguragan village as a place for collecting used junk in Cirebon district where this made Panguragan called the rongsok village